Pengaruh Pengaturan Jarak Tanam dan Defoliasi Terhadap Pertumbuhan dan Hasil Jagung Manis (Zea Mays Saccharata Sturt.) - Bagus Nur Rochman; Bayu Handoko; Gita Anggraeni (Scientific Timeline, 2022)
Sweet corn was people’s favorite among the public because it had a sweet taste and high nutritional value. Limited land ownership encourages efforts to increase plant populations without reducing yields by using narrow spacing and defoliation treatments. The research aimed to determine the best spacing for high plant density, the best defoliation technique, and the effect of interaction between spacing treatments and defoliation techniques on sweet corn plants. The results showed that spacing at high density could increase the production and productivity of sweet corn was 20 x 40 cm. Defoliation of sustain 2 and 3 could increase the cob volume. Spacing and defoliation treatments did not interact because the spacing was still optimal.